PEMBENTUKAN LAPANGAN FAKTOR DARI SUATU DAERAH INTEGRAL - Tri Widjajanti; Dahlia Ramlan; Rium Hilum (FMIPA Universitas Papua, 2009)
Ring of integers under the addition and multiplication as integral domain can be imbedded to the field of rational numbers. In this paper we make a construction such that any integral domain can be a field of quotient. The construction contains three steps. First, we define element of field F from elements of integral domain D. Secondly, we show that the binary operations in fare well-defined. Finally, we prove that f : D ® F is an isomorphisma. In this case, the polynomial ring F[x] as the integral domain can be imbedded to the field of quotient..